Trypanosome SL-RNA detection in blood and cerebrospinal fluid to demonstrate active gambiense human African trypanosomiasis infection. - Ipos Ngay Lukusa; Nick Van Reet; Dieudonné Mumba Ngoyi; Erick Mwamba Miaka; Justin Masumu; Pati Patient Pyana; Wilfried Mutombo; Digas Ngolo; Vincent Kobo; Felix Akwaso; Médard Ilunga; Lewis Kaninda; et al. (Public Library of Science (PLoS), 2021)
Background Spliced Leader (SL) trypanosome RNA is detectable only in the presence of live trypanosomes, is abundant and the Trypanozoon subgenus has a unique sequence. As previously shown in blood from Guinean human African trypanosomiasis (HAT) patients, SL-RNA is an accurate target for diagnosis. Detection of SL-RNA in the cerebrospinal fluid (CSF) has never been attempted. In a large group of Congolese gambiense HAT patients, the present study aims i) to confirm the sensitivity of SL-RNA detection in the blood and; ii) to assess the diagnostic performance of SL-RNA compared to trypanosome detection in CSF. Methodology/principal findings Blood and CSF from 97 confirmed gambiense HAT patients from the Democratic Republic of Congo were collected using PAXgene blood RNA Tubes. Before RNA extraction, specimens were supplemented with internal extraction control RNA to monitor the extraction, which was performed with a PAXgene Blood RNA Kit. SL-RNA qPCR was carried out with and without reverse transcriptase to monitor DNA contamination. In blood, 92/97 (94.8%) HAT patients tested SL-RNA positive, which was significantly more than combined trypanosome detection in lymph and blood (78/97 positive, 80.4%, p = 0.001). Of 96 CSF RNA specimens, 65 (67.7%) were SL-RNA positive, but there was no significant difference between sensitivity of SL-RNA and trypanosome detection in CSF. The contribution of DNA to the Cq values was negligible. In CSF with normal cell counts, a fraction of SL-RNA might have been lost during extraction as indicated by higher internal extraction control Cq values. Conclusions/significance Detection of SL-RNA in blood and CSF allows sensitive demonstration of active gambiense HAT infection, even if trypanosomes remain undetectable in blood or lymph. As this condition often occurs in treatment failures, SL-RNA detection in blood and CSF for early detection of relapses after treatment deserves further investigation. Trial registration This study was an integral part of the diagnostic trial "New Diagnostic Tools for Elimination of Sleeping Sickness and Clinical Trials: Early tests of Cure" (DiTECT-HAT-WP4, ClinicalTrials.gov Identifier: NCT03112655).